THE ROLE OF THE FAMILY IN FORMING A HEALTHY LIFESTYLE (Conferencea, 2023)
The socializing potential of the family in the formation of an attitude towards health and a healthy lifestyle in children and adolescents is assessed. The main behavioral risks to the health of the younger generation and the role of the immediate social environment in their minimization or aggravation are characterized.